STUDY OF AWARENESS OF TEACHERS TOWARDS NEW EDUCATION POLICY 2020 - Sharma, Sarita; Agarwal, Devendra Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
The objective of the presented research work was to study the awareness of secondary school teachers towards New Education Policy 2020 in the following context. For this, survey method has been used. In the sample, 400 secondary level teachers of Jaipur district have been selected by random method, out of which 200 are government and 200 are non-government teachers. Self-made awareness scale (in the context of new education policy) was used to study the research problem. Mean, standard deviation and t-test have been used for data analysis in the research. In conclusion, it was found that there is no significant difference between teachers of government and non-government schools in terms of awareness towards New Education Policy 2020. There is no significant difference between teachers of urban and rural schools in terms of awareness towards the New Education Policy 2020.